2014
DOI: 10.5455/2319-2003.ijbcp20140618
|View full text |Cite
|
Sign up to set email alerts
|

Immediate impact of an educational intervention on knowledge of use of disinfectants in nurses

Abstract: A structured close-ended questionnaire based on standard literature 5,6 was used. The questions were formulated to test the ability of nurses to (1) categorize commonly used medical and surgical devices (MSDs) as per modified Spaulding classification 5 (Table 1). (2) Categorize routinely available disinfectants (glutaraldehyde, hydrogen peroxide, ABSTRACT Background: Adequate disinfection and sterilization is crucial to prevent hospital acquired infections, this requires knowledge of various types of disinfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
4
3
0
Order By: Relevance
“…Our study suggests that educational intervention has positive impact on the knowledge of nurses similar to other studies [10,14]. There is a need to carry out such educational interventions periodically as in the test carried out after 1 month showed good retention of knowledge by nurses.…”
Section: Resultssupporting
confidence: 65%
“…Our study suggests that educational intervention has positive impact on the knowledge of nurses similar to other studies [10,14]. There is a need to carry out such educational interventions periodically as in the test carried out after 1 month showed good retention of knowledge by nurses.…”
Section: Resultssupporting
confidence: 65%
“…In the posttest, there is an overall increase in response similar to study done by Burute et al, [10] in both medical and surgical nurses except for the questions like uses of phenol, concentration of disinfectant to be used for different uses and special precautions to be taken while using glutaraldehyde. Knowledge about uses of phenol is important because it can be used for disinfection of urine, sputum, floor cleaning, etc., which is an important measure to prevent contamination of soil and spread of tuberculosis, etc.…”
Section: Discussionsupporting
confidence: 64%
“…Fitzpatrick M et al5 obtained similar results in their study which involved showing an instructional video to the participants on hand hygiene. Another one-day educational intervention study, focusing on disinfectant use by nurses, showed increment in the posttest scores 6. Nour-Eldein H et al7 studied same in medical students and observed that educational intervention showed statistically significant increment in the post-test scores of students in all periods of the study.…”
Section: Discussionmentioning
confidence: 97%